1) f'(x)=3x^2;
f'(x0)=3*4=12
2) f(pi/2)=y0=0;
f(x)=(1+cos2x)/2
f'(x)=-sin2x
k=f'(pi/2)=0
ур-е кас y=y0+k(x-x0)
y=0
1)
2)Уравнение касательной:
Производная:
Или можно проще:
Подставим значения в уравнение касательной:
1) f'(x)=3x^2;
f'(x0)=3*4=12
2) f(pi/2)=y0=0;
f(x)=(1+cos2x)/2
f'(x)=-sin2x
k=f'(pi/2)=0
ур-е кас y=y0+k(x-x0)
y=0
1)![f'(x)=(x^3)'-(4)'=3x^2\\f'(x_{0})=f'(2)=3*2^2=12](/tpl/images/0162/3838/6ad88.png)
2)Уравнение касательной:![y=f'(x_{0})(x-x_{0})+f(x_{0})](/tpl/images/0162/3838/b7b9d.png)
Производная:
Или можно проще:
Подставим значения в уравнение касательной: